2013
DOI: 10.1016/j.nut.2012.05.004
|View full text |Cite
|
Sign up to set email alerts
|

META060 protects against diet-induced obesity and insulin resistance in a high-fat–diet fed mouse

Abstract: META060 has potential therapeutic value for managing obesity and insulin resistance, and further research into the mechanism of action is warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 18 publications
0
14
0
Order By: Relevance
“…4. Effect of the isohumulone mixture (Meta060) and rosiglitazone intervention on obesity in the high fat fed diabetic mouse model [50].…”
Section: Influence Of the Hops-derived Isohumulones On Obesitymentioning
confidence: 99%
“…4. Effect of the isohumulone mixture (Meta060) and rosiglitazone intervention on obesity in the high fat fed diabetic mouse model [50].…”
Section: Influence Of the Hops-derived Isohumulones On Obesitymentioning
confidence: 99%
“…Extracts of the hops plant ( Humulus lupulus L. ) used as flavoring agents in beer production have been shown to reduce weight and improve glucose homeostasis in rodents [1] , [2] , [3] , [4] , [5] , [6] , [7] , [8] and humans [1] , [9] , [10] . Thus, it is of considerable interest to identify the molecular mechanisms that mediate the benefits of bioactive ingredients of hops in metabolic disease.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, this study also included a small double-blind, placebo-controlled trial in people with diabetes that showed that treatment for 8 weeks with isohumulones significantly reduced blood glucose and hemoglobin A1c levels. Subsequent studies [2] , [3] , [4] , [5] , [8] have reported positive effects of isohumulones in reducing weight gain and fat mass, improving glucose homeostasis and insulin sensitivity, decreasing liver lipid accumulation, and reducing plasma triglycerides in multiple rodent models (e.g., DIO, KK- A y , db/db mice, Wistar rats). Notably, a larger clinical trial in Japanese subjects with prediabetes showed that 12-week treatment with isohumulones significantly reduced body weight, body mass index, fat mass, fasting blood glucose, and hemoglobin A1c levels [9] .…”
Section: Introductionmentioning
confidence: 99%
“…Studies in animal models of type 2 diabetes show that rosiglitazone improves glycaemic control by enhancing insulin‐stimulated whole‐body glucose uptake (Zheng, Shao, Wu, Shen, & Lin, ). It has been reported that rosiglitazone has an ability of enhancing metabolic flexibility of various tissues, including muscle, liver, adipose and bone tissue (Stage et al, ; Vroegrijk et al, ). Much evidence exists to suggest that rosiglitazone could influence male germinal cells (Rabbani, Devi, & Khanam, ).…”
Section: Introductionmentioning
confidence: 99%